(1Z,4Z)-dimethyln'1,N'4-BIS(2,4-dinitrophenyl)terephtha lohydrazonate: A Novel Schiff Base with its Co(II) and Cd(II) Complexes, Structural Investigations to Biological Potential - Pinky; Rani, Anita; Dhiman, Pooja; Varol, Mehmat; Tuli, Hardeep Singh; Siwach, Priyanka; Kumar, Manoj (Anti-Infective Agents, 2026)
AimsThe purpose of this study was to develop and evaluate novel antimicrobial Schiff base and its transition metal complexes.IntroductionAntibiotics that were often used to treat microorganisms are no longer effective against them because of developed resistance. It is believed that newly developed Schiff bases and their transition metal complexes could function well as antimicrobial agents and have considerable pharmacological efficacy.MethodsIn this study new Schiff base ligand was synthesized by taking the 1:1 stoichiometric ratio of 2, 4-dinitrophenyl hydrazine and dimethyl tetraphthalate, with ethanol serving as the solvent subsequently its Co (II) and Cd (II) Complexes were created by reacting the synthesized Schiff base ligand with the corresponding metal salts in the form of chlorides.Results and DiscussionAll of the target compounds' structures were evaluated using sophisticated analytical techniques, such as elemental analysis, FT-IR, 1H and 13C NMR, and LCMS. In order to determine each compound's biological potential as an antimicrobial agent, its effectiveness was also assessed. The results of the molecular docking studies were found to be compatible with biological potential. At concentrations of 100–250 ppm, the zones of inhibition were observed to be between 9–20 mm for ligands and 10-23 mm for complexes. The outcome showed that, in comparison to the Schiff base ligand, metal complexes have superior biological activity.ConclusionThe current study provided a unique method for creating novel and physiologically active Schiff bases and their transition metal complexes. The findings demonstrate that the compounds produced are a promising antimicrobial mediator against contemporary human illnesses. Additionally, it may pave the way for further research on drug-resistant microbes with potential biological applications.
Keywords: spectral investigations